Reality Therapy untuk meningkatkan penerimaan diri pada perempuan dewasa dengan masalah relasional - Wa Ode Nursanaa (Universitas Muhammadiyah Malang, 2021)
Relationship problems can come from parent-child relationships, with siblings, with a spouse, parenting styles from parents, family divorce, and several other factors. Relationship problems can result in low self-acceptance. The purpose of this case study is to see if Reality Therapy can improve self-acceptance due to relationship problems. The assessments carried out to diagnose the subject are interviews, observation, graphic tests (DAP, BAUM, HTP), SSCT, CFIT, and the Self-Acceptance Scale. The intervention carried out was using Reality Therapy. The results of the intervention showed that Reality Therapy had a positive and effective impact on increasing self-acceptance in the subject. The subject can know his strengths and weaknesses and is able to make positive plans for himself.